Analisis Kualitas Layanan My Pertamina Menggunakan Pendekatan e-GovQual pada Beberapa Kota Percobaan - Nina Kurnia Hikmawati (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2022)
My Pertamina is an e-government application, launched as a loyalty and e-payment program that is expected to implement cashless transactions. In addition, My Pertamina is used to sell subsidized fuel so that it is right on target. Apparently this is still being discussed by various parties. The quality of this application, needs to be analyzed from the responses of users in the 11 cities of the trial district phase 1. The dataset used is responses from 100 users who were collected through a questionnaire. The method used to analyze service quality and determine the influencing variables is e-GovQual then validity and reliability testing is carried out with each result being 100% and 94.6%, which means that the questionnaire formed is valid and reliable to be used in this study. The analysis carried out on the results of filling out the questionnaire using multiple linear analysis with the results of the coefficient of determination shows that the dependent variable (Y) can be influenced by the independent variable (X) by 97.7%, while the remaining 2.3%. As for the correlation value of 0.989 or 98.9%, this means that there is a very strong influence between the quality of My Pertamina's services on user satisfaction. In addition, the results of hypothesis testing show that all hypotheses can be accepted because they have a positive and significant effect. Thus, the quality of Mypertamina's services can be maintained to support the government's program.